Q-linear functions, functions with dense graph, and everywhere surjectivity - García-Pacheco, F. J.; Rambla-Barreno, F.; Seoane-Sepúlveda, J. B. (Mathematica Scandinavica, 2008)
Let L, S and D denote, respectively, the set of Q-linear functions, the set of everywhere surjective functions and the set of dense-graph functions on R. In this note, we show that the sets D(S L), S L, S L and DL S are lineable. Moreover, all these sets contain (omitting zero) a vector space of the biggest possible dimension, 2^c.